EFEITOS DA TERAPIA COGNITIVO-COMPORTAMENTAL ASSOCIADA A PROBIÓTICOS NO TRATAMENTO DE PACIENTES DEPRESSIVOS - Silva, Marcielle Toaldo da (2024)
Depression is a highly prevalent mental disorder with an unpredictable course, characterized by persistent feelings of sadness and low self-esteem, disturbed appetite, insomnia, anxiety and suicidal thoughts. According to the World Health Organization (2024), the disorder is highly prevalent and with high impact on public health, with more than 300 million people affected worldwide. Pharmacotherapy uses oral first and second generation antidepressants, which undergo extensive first-pass metabolism, resulting in hepatic degradation of the drug, reducing its availability in the blood and leading to a delay in the onset of the therapeutic effect, often with reduced efficacy. Psychotherapy is an important adjunct in the treatment of depression, specially the Cognitive-Behavioral Therapy (CBT) approach has evidence of efficacy in helping people to restructure their cognitions and learn ways to solve problems, leading to significant changes in depressed mood and recurrent thoughts and dysfunctional behaviors. However, there are individual limitations due to the etiology and course of the disease, and in this way, studies indicate the involvement of systemic factors in the mechanisms of depressive disorder, mainly Major Depressive Disorder. Studies in animal models indicate a beneficial effect of treatment with pre- and probiotics on depressive-type symptoms. In humans, there is a clear change in the colony of bacteria present in the intestinal flora, but the evidence are been studied to support the use of probiotics as an adjuvant treatment to reduce the symptoms of Major Depressive Disorder. Dysbiosis alters the production of intestinal neurotransmitters, alters the production of pro-inflammatory cytokines, creating an environment with a negative effect on the gut-brain axis. On the other hand, alterations in the production of brain neurotrophins can influence the axis and thus have a negative effect on the intestinal flora. In this sense, treatment with probiotics has been recommended by professionals, but few studies have been carried out to confirm its effectiveness alone or in combination with other therapies. In the present study, people with Major Depressive Disorder treated at a health unit in the interior of the state of Rio Grande do Sul, Brazil, who were undergoing pharmacotherapy and CBT, were given probiotics and followed up for six months. The reduction in the participants' depressive and anxiety symptoms was verified by analyzing the results of the Hamilton Anxiety Scale and the Hamilton Depression Scale, as well as biomarker analysis. The results presented provide evidence of the beneficial role of probiotics in patients diagnosed with depression, as an adjuvant that can help reduce symptoms of depression in people undergoing psychopharmacological treatment and CBT. However, despite the evidence, more studies are still needed to verify the appropriate strains and the ideal therapeutic quantities to be used in this type of treatment, in order to better verify its effectiveness.